Association of G6PD variants with hemoglobin A1c and impact on diabetes diagnosis in East Asian individuals. Issue 1 (24th March 2020) - Leong, Aaron; Lim, Victor Jun Yu; Wang, Chaolong; Chai, Jin-Fang; Dorajoo, Rajkumar; Heng, Chew-Kiat; van Dam, Rob M; Koh, Woon-Puay; Yuan, Jian-Min; Jonas, Jost B; Wang, Ya Xing; Wei, Wen-Bin; et al.
Abstract : Objective: Hemoglobin A1c (HbA1c) accuracy is important for diabetes diagnosis and estimation of overall glycemia. The G6PD- Asahi variant which causes glucose-6-phosphate dehydrogenase (G6PD) deficiency has been shown to lower HbA1c independently of glycemia in African ancestry populations. As different G6PD variants occur in Asian ancestry, we sought to identify Asian-specific G6PD variants associated with HbA1c. Research design and methods: In eight Asian population-based cohorts, we performed imputation on the X chromosome using the 1000 Genomes reference panel and tested for association with HbA1c (10 005 East Asians and 2051 South Asians). Results were meta-analyzed across studies. We compared the proportion of individuals classified as having diabetes/pre-diabetes by fasting glucose ≥100 mg/dL or HbA1c ≥5.7% units among carriers and non-carriers of HbA1c-associated variants. Results: The strongest association was a missense variant ( G6PD -Canton, rs72554665, minor allele frequency=2.2%, effect in men=−0.76% unit, 95% CI −0.88 to −0.64, p=1.25×10 −27, n=2844). Conditional analyses identified a secondary distinct signal, missense variant ( G6PD -Kaiping, rs72554664, minor allele frequency=1.6%, effect in men=−1.12 % unit, 95% CI −1.32 to −0.92, p=3.12×10 −15, pconditional_Canton =7.57×10 −11 ). Adjusting for glucose did not attenuate their effects. The proportion of individuals with fasting glucose ≥100 mg/dL did not differ by carrier status of G6PD -Canton (p=0.21). Whereas the proportion of individuals with HbA1c ≥5.7% units was lower in carriers (5%) compared with non-carriers of G6PD -Canton (30%, p=0.03). Conclusions: We identified two G6PD variants in East Asian men associated with non-glycemic lowering of HbA1c. Carriers of these variants are more likely to be underdiagnosed for diabetes or pre-diabetes than non-carriers if screened by HbA1c without confirmation by direct glucose measurements.